1989
DOI: 10.1111/j.1365-2222.1989.tb02762.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of occupational asthma

Abstract: Summary Accurate diagnosis of occupational asthma takes time, enthusiasm and a particular knowledge of the work situation, as well as expertise in the use of diagnostic procedures. The prognosis of patients with occupational asthma is probably improved by removing them from the responsible agent as soon as possible after sensitization occurs. However, it is much easier to make the diagnosis while the worker is still exposed to the cause of the problem. Early referral for expert investigation is therefore impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…18,20,23,26,27 Some evidence exists which suggests that the onset of sensitization occurs after a mean exposure interval of 2 years. 28 After sensitization, any exposure, even to levels below any occupational exposure limit or standard, can produce an asthmatic response which may be life threatening. This asthmatic reaction may occur minutes after exposure (immediate), several hours after exposure (late), or a combination of both immediate and late components after exposure (dual).…”
Section: Diisocyanate-induced Sensitizationmentioning
confidence: 99%
“…18,20,23,26,27 Some evidence exists which suggests that the onset of sensitization occurs after a mean exposure interval of 2 years. 28 After sensitization, any exposure, even to levels below any occupational exposure limit or standard, can produce an asthmatic response which may be life threatening. This asthmatic reaction may occur minutes after exposure (immediate), several hours after exposure (late), or a combination of both immediate and late components after exposure (dual).…”
Section: Diisocyanate-induced Sensitizationmentioning
confidence: 99%
“…18,20,23,26,27 Some evidence exists which suggests that the onset of sensitization occurs after a mean exposure interval of 2 years. 28 After sensitization, any exposure, even to levels below any occupational exposure limit or standard, can produce an asthmatic response which may be life threatening. This asthmatic reaction may occur minutes after exposure (immediate), several hours after exposure (late), or a combination of both immediate and late components after exposure (dual).…”
Section: 21mentioning
confidence: 99%
“…A private consultant assessed employee exposures to copper, hydrogen fluoride, varnish makers and painters naphtha, xylenes, and TDI at Square D Company on July [15][16]1992. Their report dated August 18, 1992, showed that all exposures were below the Occupational Safety and Health Administration (OSHA) Permissible Exposure Limits (PELs) and Short-Term Exposure Limits (STELs).…”
Section: Previous Evaluations Previous Evaluations Previous Evaluatiomentioning
confidence: 99%
“…5,7,10,13,14 Some evidence exists which suggests that the onset of sensitization occurs after a mean exposure interval of 2 years. 15 After sensitization, any exposure, even to levels below any occupational exposure limit or standard, can produce an asthmatic response which may be life threatening. This asthmatic reaction may occur minutes after exposure (immediate), several hours after exposure (late), or a combination of both immediate and late components after exposure (dual).…”
Section: Diisocyanates (Tdi) Diisocyanates (Tdi) Diisocyanates (Tdi) mentioning
confidence: 99%
See 1 more Smart Citation